2014
DOI: 10.1007/s12155-014-9440-x
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae Versus Land Crops as Feedstock for Biodiesel: Productivity, Quality, and Standard Compliance

Abstract: Despite certain environmental advantages over fossil diesel, land crop-derived biodiesels may not satisfy the increasing worldwide demand for transportation fuels. As an abundant photosynthesizer, algae could be an adequate surrogate for biodiesel production. Nevertheless, high production costs, scarce selected species, and inaccurate assumptions about production yields represent industrial uncertainties. In this study, a reliable approach to analyzing algal biodiesel production has been developed based on spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 39 publications
2
46
0
3
Order By: Relevance
“…This result shows the suitability of Botryococcus oil to biodiesel production. Similar results were achieved in previous works with B. terribilis and B. braunii IBL [6,24,25].…”
Section: Methyl Ester Profile and Applicability For Biodieselsupporting
confidence: 91%
See 2 more Smart Citations
“…This result shows the suitability of Botryococcus oil to biodiesel production. Similar results were achieved in previous works with B. terribilis and B. braunii IBL [6,24,25].…”
Section: Methyl Ester Profile and Applicability For Biodieselsupporting
confidence: 91%
“…Previous research papers showed that microalgae can accumulate most of its lipids in the form of FA [8]. Furthermore, the FA profile determines the biodiesel quality parameters [24,25,27]. The authors acknowledge the disadvantages of Botryococcus in comparison with other microalgae strains.…”
Section: Methyl Ester Profile and Applicability For Biodieselmentioning
confidence: 90%
See 1 more Smart Citation
“…The farming of microalgae as potential raw material for the production of biodiesel has thus expanded rather quickly in recent decades. However, production of biodiesel from microalgae was never shown economically competitive because of high costs associated with agglutination, centrifugation, drying and lysis of cells for extraction of lipids (Demirbas and Demirbas, 2011;Nascimento et al, 2014). In this scenario, research on the use of microalgae by the pharmaceutical and cosmetics industries, human and animal nutrition has gained grounds in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies indicated that fungi have advantages of simultaneously utilizing multiple carbon sources (glucose and xylose) as well as better tolerance to inhibitors (furfural, hydroxymethylfurfural (HMF), and aromatic compounds) in lignocellulosic hydrolysates (Ruan et al, 2012(Ruan et al, , 2013. The lipid content in oleaginous fungi ranges from 21% to 74%, which is also comparable to most oleaginous yeasts and microalgae (Nascimento et al, 2014;Ruan et al, 2012). Therefore, the exploitation of fungal lipid is important for the development of microbial biodiesel production on lignocellulosic feedstocks.…”
Section: Introductionmentioning
confidence: 99%